Corrosion protective mechanism of smart graphene-based self-healing coating on carbon steel. (September 2020) - Ye, Yuwei; Chen, Hao; Zou, Yangjun; Ye, Ying; Zhao, Haichao
Highlights: Graphene porous polyhedral oligomeric silsesquioxane framework was synthesized. Benzotriazole was successfully loaded in the porous structure of graphene. Load rate, release rate and self-healing mechanism of smart coating were stated. Abstract: Graphene sheets containing porous polyhedral oligomeric silsesquioxane (POSS) framework were synthesized as nanocontainer for self-healing organic coating. The corrosion inhibitor of benzotriazole (BTA) was loaded into the porous graphene sheets and then imbedded into epoxy coating to form composite coating. Results showed that the composite coating exhibited excellent self-healing capacity due to the spontaneous release from graphene-based nanocontainer. Through analysis, the effective protective effect of coating contained two aspects. First, the BTA could be released from the nanocontainer to form an adsorption layer on metal surface. Second, the physical barrier of graphene could greatly suppress the permeation of corrosion medium.